The Gospel of John: A Commentary. 2 volumes. By Craig S. Keener. Pp. xlviii + 1636. Peabody, MA: Hendrickson Publishers, 2003. isbn 1 56563 378 4. £57.95 - Edwards, Ruth B. (The journal of theological studies, 2005)
This is a massive commentary on John's Gospel, in length rivalling Schnackenburg's magnum opus on this subject and outdoing Raymond Brown's. Its author, Craig S. Keener (Professor of New Testament at Eastern Seminary, Philadelphia), will be known to many readers for his work on Matthew, Revelation, and aspects of Pauline theology. He writes from a conservative viewpoint, while paying attention to other critical approaches and citing from a wide range of primary and secondary literature. At times I felt conservative views were overemphasized and radical ones too lightly dismissed., The Introduction (330 pp., with 424 footnotes) could have been a book in itself.